PERLINDUNGAN KONSUMEN TERHADAP PENGGUNA JASA PENGIRIMAN BARANG (EKSPEDISI) TERKAIT KEHILANGAN PAKET - Manurung, Irwan Midian; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
This research aims to identify consumer protection related to users of goods delivery services (expeditions) in the event of loss of consumer packages and to find out how the process of resolving compensation for losses is carried out by business actors, in this case goods delivery service companies (expeditions), to consumers on the basis of reports. consumer complaints at the National Consumer Protection Agency (BPKN). Consumer protection is all efforts that ensure legal certainty to provide protection to consumers. This writing uses normative legal research with secondary data in the form of books, journals, literature reviews and uses statutory regulations as the main source of information. Compensation for losses related to lost goods made by goods delivery (expedition) service companies to consumers must be in accordance with or equivalent to the value of the goods lost and the provisions for the inclusion of standard clauses by business actors regarding compensation must be adjusted because they are considered a form of transfer of responsibility of business actors. Recommendations for consumers to make a consumer complaint report to the National Consumer Protection Agency (BPKN) if they receive inappropriate compensation so that the National Consumer Protection Agency (BPKN) carries out its function of providing advice and recommendations to the government in the context of formulating policies in the field of consumer protection.Keywords: Consumer Protection, Expedition, Compensation, BPKN.